The Open Data of Institutional Advertising - Tapia López, Alicia; Marín Palacios, Cristina (Revista General de Información y Documentación, 2018)
The aim of this study is to analyze the structure and content of open data on institutional advertising appearing in Spanish municipal open data portals. We selected those portals that gather data on advertising and created an annual index for each municipality to compare the evolution of this spending from 2006 to 2017. The results reveal that the release of data concerning this type of publicity is given a low profile. Additionally, the data are structured in non-standardized fashion and lack certain relevant information. Change is required in these practices in light of the close relationship perceived between institutional advertising, municipal elections, and the citizenry.